PERAWATAN SETELAH KEMATIAN DALAM BUDAYA SUKU BATAK TOBA: STUDI ETNOGRAFI - Idauli Simbolon; Albinur Limbong (NUTRIX, 2022)
Abstract Various cultural and religious traditions and practices associated with death. The nurse must ensure that any ritual is implied according to the client's belief and culture. The purpose of the study is to explore the cultural activities of care after the death of Christian elderly in Batak Tobanese culture in Indonesia. Method of this study is qualitative with an ethnography approach. Data is obtained by in-depth interviews with six traditional kings of the Batak Tobanese tribe. Informants were approached by snowballing. Data were analyzed using content analysis. Several themes and categories emerged: the level of death, personal care, position of the hands, wailing, piece of linen (Ulos), and cemetery. Care after death in Batak Tobanese culture is very unique and different from other tribes. Each symbol implies important meaning. Inappropriate in executing the meaning of these symbols may cause problems in the funeral procession. Therefore, nurses responsible for providing appropriate handling start from the beginning such as personal care and proper hand position according to the level of the death before the dead body is discharged from hospital. Key word: after death, Batak Toba, Care Abstrak Berbagai tradisi dan praktik budaya dan agama terkait dengan kematian. Perawat harus memastikan bahwa setiap ritual diaplikasikan sesuai dengan keyakinan dan budaya klien. Tujuan dari penelitian ini adalah untuk mengeksplorasi kegiatan budaya perawatan setelah kematian lansia Kristen dalam budaya Batak Toba di Indonesia. Metode penelitian ini adalah kualitatif dengan pendekatan etnografi. Data diperoleh dengan wawancara mendalam dengan enam raja adat suku Batak Toba. Informan didekati dengan cara snowballing. Data dianalisis menggunakan analisis isi. Beberapa tema dan kategori muncul: tingkat kematian, perawatan, posisi tangan, ratapan, kain ulos, dan kuburan. Perawatan setelah kematian dalam budaya Batak Toba sangat unik dan berbeda dengan suku-suku lainnya. Setiap simbol menyiratkan makna penting. Ketidaktepatan dalam melaksanakan makna simbol-simbol tersebut dapat menimbulkan masalah dalam prosesi pemakaman. Oleh karena itu, perawat bertanggung jawab untuk memberikan penanganan yang tepat mulai dari awal seperti perawatan diri dan posisi tangan yang tepat sesuai dengan tingkat kematian sebelum jenazah dipulangkan dari rumah sakit. Key word: Batak Toba, Perawatan, Setelah Kematian